2021
DOI: 10.3889/oamjms.2021.5850
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Chondrogenesis in Hypoxic Precondition Culture: A Systematic Review

Abstract: BACKGROUND: Cartilage tear has begun to be treated with stem cells. However, stem cell oxygen level culture has not been evaluated for the best environment to enhance chondrogenesis. AIM: The purpose of this review is to focus on the hypoxic oxygen level of stem cells culture as a treatment for cartilage tear. METHODS: A literature search was systemically conducted on PubMed (MEDLINE), OVID, EMBASE, the Cochrane Library, Scopus, Web of Science, Science Direct, Wiley Online Library, Google Scholar, and bibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Research have not yet reported significant differences in the use of animal-derived or synthetic biomaterials. Several lines of evidence suggest that synthetic materials have a lower risk of disease transmission (Barakat et al 2008, Rhatomy et al 2021. Deproteinization is an essential process to eliminate the antigenicity of xenograft bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research have not yet reported significant differences in the use of animal-derived or synthetic biomaterials. Several lines of evidence suggest that synthetic materials have a lower risk of disease transmission (Barakat et al 2008, Rhatomy et al 2021. Deproteinization is an essential process to eliminate the antigenicity of xenograft bone.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, the BCPRF can be developed as an alternative implant capable of replacing the use of autologous cartilage. Rhatomy et al (2021) stated that decellularized biomaterial scaffold limits the use of growth factor, resulting in better cost and resource efficiency. Organic materials are preferred because they have better biocompatibility and biodegradability than synthetic materials (Park & Cho 2010).…”
Section: Introductionmentioning
confidence: 99%
“…T A B L E 3 Tools and instruments used in the included studies (n = 82). ,59,[65][66][67]69,71,73,74,76,77,[79][80][81]83,84,87,89,[91][92][93][94]96,98,100,102,107,[109][110][111][112]114,115,[118][119][120][121][122][123][124][125][127][128][129][130][131][132]136 : CONSORT, Consolidated Standards of Reporting Trials; GRADE, Grading of Recommendations Assessment, Development and Evaluation; OHAT, Oral Health Assessment Tool; SYRCLE, Systematic Review Centre for Laboratory Animal Experimentation; ToxRTool, Toxicological data Reliability Assessment Tool.…”
mentioning
confidence: 99%